Ethnobotanical study of pumpkin (Cucurbita moschata Duchesne) landraces in Benin - Vincent Ezin; Ulrich Herbert Gbemenou; Gazali B. T. A. Sanni; Adam Ahanchede (CABI Agriculture and Bioscience)
Abstract Background Pumpkin, Cucurbita moschata Duchesne, is important food resource due to their nutritional composition. Despite their food advantages, they still remain underutilized crops in Africa and particularly in Benin. No documented information is available on the knowledge of producers on the use, conservation and commercialization of Cucurbita moschata. The objectives of this study are to (i) collect various accessions of pumpkin on the basis of local taxonomic criteria in Benin; (ii) collect information on uses of pumpkin in Benin. To this end, an investigation was carried out in the departments of Couffo (Dogbo, Djakotomey, Klouékanme and Aplahoué) and Borgou (Parakou and N’dali). Methods One hundred twenty (120) farmers grouped into 06 different ethnic groups (Adja, Bariba, Bialy, Fon, Gourmantché and Zarma) were interviewed. Six pumpkin landraces were identified in 19 villages surveyed through systematic census of farmers supported by the snowball technique. Results Varietal diversity on a municipal level varied from two to four. Pumpkin was mainly cultivated by men and about 15% were cultivated in cultural association with maize, cassava, cowpea and groundnut. The harvested fruits were used for consumption, commercial, therapeutic and occult purposes. However, about 48% of producers have abandoned its production mainly due to production and marketing constraints. This abandonment could induce a risk of genetic erosion of this species. Thus, the conservation and an enhancement of the genetic resources of this species is essential. Conclusions This study made it possible to establish farmers’ knowledge on the utilization and production of pumpkin landraces, and identify the varietal diversity of Benin landraces of pumpkin.